The Influence of Corporate Social Responsibility in Mediating Relationships Green Accounting on Financial Performance - Anggela Sukma Pratiwi; Raudhatul Hidayah (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Improving financial performance is the main goal of every company. However, the company's operations are always related to the depletion of natural resources, which causes environmental damage. Green accounting efforts are made to preserve the environment. This study aims to determine the effect of CSR disclosure in mediating green accounting (environmental performance and environmental costs) on financial performance. The research sample consisted of 85 observations of non-financial sector companies listed on the Indonesian stock exchange and participating in the Ministry of Environment's PROPER for the 2019-2021 period by purposive sampling. SEM PLS path regression was used to test the direct and indirect effects of 7 hypotheses using the SmartPLS 4.0 statistical tool. research results show evidence that environmental performance has a significant positive effect on financial performance; Environmental cost has a significant positive effect on company performance; environmental performance has no significant effect on CSR disclosure; Environmental cost has no significant effect on CSR disclosure; Disclosure of CSR has a significant positive effect on financial performance; CSR is not able to mediate green accounting on financial performance. The research findings show that environmental performance, environmental costs, and CSR disclosure on company websites have an effect on improving financial performance. So companies need to consider making decisions about disclosing these items on the company's website in an effort to improve financial performance and a positive image in society.